Integrity in scientific research : creating an environment that promotes responsible conduct - Committee on Assessing Integrity in Research Environments (U.S.); National Research Council (U.S.); United States. Office of the Assistant Secretary for Health. Office of Research Integrity (Washington, D.C. : National Academies Press, 2002)
"Integrity in Scientific Research attempts to define and describe those elements that enable and encourage individuals involved with scientific research to act with integrity. Providing a framework for research and educational institutions, this important book will be essential for anyone concerned about ethics in the scientific community."--Jacket
Executive summary -- 1. Introduction -- 2. Integrity in research -- 3. The Research environment and its impact on integrity in research -- 4. Institutional approaches to fostering integrity in research -- 5. Promoting integrity in research through education -- 6. Evaluation by self-assessment -- 7. Concluding remarks and recommendations -- Appendixes.
Includes bibliographical references and index.
"Support for this project was provided by the Office of Research Integrity, U.S. Department of Health and Human Services."--Title page verso
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Keywords: Research -- Moral and ethical aspects; Integrity; Fraud in science; Research -- standards; Ethics; Research Personnel; Ethics, Institutional; Social Control, Informal; Scientific Misconduct; United States; Recherche -- Aspect moral; Intégrité.; Fraude scientifique; BUSINESS & ECONOMICS -- Business Ethics; Fraud in science; Integrity; Research -- Moral and ethical aspects; Integriteit; Onderzoek; Wetenschapsbeleid; 02.15 science policy, cultural policy; Wissenschaftsethik; Integrity